Characterizing Federally Mandated Early Intervention for Children with Social Communication Delays: A Mixed-Methods Analysis - Yael G. Dai; Kyle M. Frost; Ellie M. Harrington; Yael Stern; Emily R. Britsch; Brooke R. Ingersoll; Allison Wainer; Wendy L. Stone; Sarabeth Broder-Fingert; Alice S. Carter (Behavioral Sciences)
The most common way for children with social communication delays to receive intervention before age three in the United States is through Part C early intervention (EI). Part C was designed to take a multidisciplinary approach to address a range of developmental domains. The type of intervention delivered in Part C EI has rarely been examined through direct observation. Our team conducted a mixed-methods analysis to characterize EI sessions by 33 providers across four states. Specifically, we describe the quantity and quality of caregiver coaching based on provider report and researcher coding of EI session content. Eligible providers conducted weekly EI sessions with at least one child with social communication delays. Providers self-reported greater use of caregiver coaching relative to the video coding conducted by researchers. While there were similarities in session topics, presumed goals, and intervention strategies used across providers, differences were observed in session duration, session location, and caregiver engagement in session. This study begins to fill a substantial gap by illuminating the types of interventions children with social communication delays receive in federally mandated Part C. It also highlights the need for more specialized training and standardization in EI practices to ensure that children with social communication delays and their caregivers benefit from the most efficacious interventions during a critical time of increased brain plasticity.